Access for Augustus: The 'House of Livia' and the Palatine Passages. (November 2022) - Wiseman, T. P.
Abstract: This article draws attention to a neglected archaeological datum (pointed out by Amanda Claridge in 2014) that has important consequences for our understanding of the Augustan Palatine. The 'house of Livia', excavated in 1869, has always been thought of as belonging to the Augustan complex, but the evidence suggests that it did not exist above ground level after the 30s b.c .; its basement, on the other hand, was connected with an underground passage that was evidently an integral part of the building project begun by Imperator Caesar ('Octavian') in 36 b.c . Claridge's argument, with its corollary, that the Apollo temple faced north-east to the summit plateau of the hill, explains the surviving textual sources much more satisfactorily than the current orthodoxy. In particular, it casts significant new light on Suetonius' statement that the name 'Augustus' referred to Romulus' augustum augurium at the foundation of the city.